Psychedelic Cognition—The Unreached Frontier of Psychedelic Science - Bălăeţ, Maria (Frontiers in Neuroscience, 2022)
Psychedelic compounds hold the promise of changing the face of neuroscience and psychiatry as we know it. There have been numerous proposals to use them to treat a range of neuropsychiatric conditions such as depression, anxiety, addiction and PTSD; and trials to date have delivered positive results in favour of the novel therapeutics. Further to the medical use, the wider healthy population is gaining interest in these compounds. We see a surge in personal use of psychedelic drugs for reasons not limited to spiritual enhancement, improved productivity, aiding the management of non-pathological anxiety and depression, and recreational interests. Notably, microdosing – the practice of taking subacute doses of psychedelic compounds – is on the rise. Our knowledge about the effects of psychedelic compounds, however, especially in naturalistic settings, is still fairly limited. In particular, one of the largest gaps concerns the acute effects on cognition caused by psychedelics. Studies carried out to date are riddled with limitations such as having disparate paradigms, small sample sizes, and insufficient breadth of testing on both unhealthy and healthy volunteers. Moreover, the studies are majoritarily limited to laboratory settings and do not assess the effects at multiple dosages within the same paradigm nor at various points throughout the psychedelic experience. This review aims to summarise the studies to date in relation to how psychedelics acutely affect different domains of cognition. In the pursuit of illuminating the current limitations and offering long-term, forward-thinking solutions, this review compares and contrasts findings related to how psychedelics impact memory, attention, reasoning, social cognition, and creativity.